Un colonisateur atypique : Hubert Lyautey Sa politique de mission civilisatrice - Krajcsovszki, Monika (Études sur la Région Méditerranéenne, 2022)
The name of Marshal Hubert Lyautey (1854–1934) is closely associated with that of protectorate. Born into a family with a great military tradition, he became a model of the “great colonial”. He was a royalist embracing the mission of keeping and growing the French Empire of the Republic. Following a journey to Algeria and his first service in Indo-China between 1894 and 1897, he decided to make his career in the colonies. He served with Colonel Joseph Gallieni who introduced him to the ideas and practices of a new type of colonial administration, the politics of association instead of the politics of assimilation. Through the works of theoreticians such as Jean-Marie de Lanessan, Joseph Chailley-Bert and Jules Harmand, he deepened these new ideas. The doctrine of the protectorate of Lyautey was formed at the beginning of his colonial career. He became a spokesman for the politic of association which is based on indirect administration and on the application of the natives in the administration of the colonies.